Application of Digital Maps in Land Use (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the results of the inventory of land owned by land users and tenants in the Karavulbazar district of the Bukhara region, identifying the problems and shortcomings identified during the inventory. The innovative technologies used in the census, the importance of statistical data in the system of rational and efficient use of land resources, the preparation of digital maps based on the data obtained during the census, and the use of these digital maps in the field of national economy. It has been suggested that it be used.